Analysis of Internal and External Factors in Business Development Strategy - Radha Niska Fratama; Siti Jahroh; Heny Kuswanti Suwarsinah (LPPM Institut Bisnis dan Informatika Kesatuan, 2025)
The popularity of Japanese food has increased in Indonesia, particularly in Bogor, creating both opportunities and challenges for micro, small, and medium enterprises. This study examines a small enterprise offering takoyaki and okonomiyaki near a university campus to enhance its business performance. The goal is to analyze internal and external factors, develop strategies, and identify the best approaches for growth. The research used surveys, interviews, and observations from December 2024 to March 2025, involving customers, employees, and local stakeholders, with various analysis tools to process the data. Findings show strengths, such as its location and customer loyalty, but also weaknesses like pricing and operational issues. Opportunities include a growing student market, while threats involve competition and substitutes. The business is positioned to maintain its market share while exploring growth, with top strategies like campus promotions and price adjustments. In conclusion, applying these strategies can help boost competitiveness and achieve long-term success in the Japanese food market by addressing weaknesses and adapting to trends.